Birds Diversity in Tayawiâs Watersheed Area Aketajawe-Lolobata National Park (Keragaman Jenis Burung di DAS Tayawi Taman Nasional Aketajawe-Lolobata) - Arini, Diah Irawati Dwi; Kinho, Julianus (Balai Penelitian Kehutanan Manado, 2014)
Aketajawe-Lolobata National Park was selected as one of conservation areas in Indonesia due to its important roles to preserve wildlife natural resources and its unique ecosystem. Our research on fauna diversity was designed to identify bird species diversity that inhabited Tayawiâs watershed within the Aketajawe-Lolobata National Park in North Maluku. We explored the area by using transect method; species identification was carried out by visual and vocal encounter. Fifty five bird species were identified and they belong to 25 families. Among them, 17 species were identified as endemic to Maluku and Halmahera islands. Based on our analysis and field observation, these areas had low fauna diversity. We suspected that illegal logging and hunting might have caused a rapid decrease of the bird population in Tayawiâs watershed area. These can be a serious threat if it is not well-anticipated. Therefore, urgent need is required to discontinue the activities of illegal logging and hunting.